Personality traits and language learning attitudes among college student - Harison Mohd Sidek (Pusat Perkembangan Pelajar ,U.K.M, 2009)
The purpose of the study was to examine out the existing language attitudes among first year English as a Foreign Language (EFL) college students using five personality traits namely self-image, inhibition, risk-taking, ego-permeability and tolerance for ambiguity as language attitude indicators. In addition, the challenges that EFL teachers have in dealing with developing language attitudes among students as well as factors that may influence the formation of language attitudes among students were also unravelled. Besides student-survey, interviews with teachers and student participants were also conducted to gain more comprehensive insights into EFL students’ attitudes with regards to learning. The results indicated that the participants demonstrated low self-image, high inhibition, low risk-taking, high ego-permeability and low tolerance for ambiguity in learning EFL. The findings from teacher and student interviews were congruent with the personality traits that emerged from the survey data. Discussion was focused on how instruction may help improve EFL learners’ language attitudes towards learning.